2017
DOI: 10.1037/pha0000140
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette user plasma nicotine concentration, puff topography, heart rate, and subjective effects: Influence of liquid nicotine concentration and user experience.

Abstract: Electronic cigarette (ECIG) nicotine delivery and other effects may depend on liquid nicotine concentration and user experience. This study is the first to examine systematically the influence of ECIG liquid nicotine concentration and user experience on nicotine delivery, heart rate, puff topography, and subjective effects. Thirty-three ECIG-experienced individuals and 31 ECIG-aïve cigarette smokers completed four laboratory conditions that consisted of two, 10-puff bouts (30-second IPI) with a 3.3 volt ECIG b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
183
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(211 citation statements)
references
References 42 publications
25
183
3
Order By: Relevance
“…For example, by not keeping the ECIG liquid consistent, these early pre-clinical studies were unable to determine if variability in toxicant yields across devices were in fact due to differences in a particular device characteristic (e.g., battery voltage) or the result of the nicotine concentration and/or flavorings differing across the liquids used to generate the aerosols. Furthermore, the puffing parameters used by these early pre-clinical studies to generate ECIG aerosols were consistent with that of a tobacco cigarette smoker, but other studies have demonstrated that the puff topography of an experienced ECIG user may differ markedly from that of a tobacco cigarette smoker (Hiler et al, 2017;Spindle et al, 2015). Thus, by not using puffing parameters representative of an experienced ECIG user, the toxicant content of the aerosols generated in these early pre-clinical studies may not be indicative of an ECIG user's actual toxicant exposure.…”
Section: Pre-clinical Analytical Chemistry Examinations Of Ecigssupporting
confidence: 55%
“…For example, by not keeping the ECIG liquid consistent, these early pre-clinical studies were unable to determine if variability in toxicant yields across devices were in fact due to differences in a particular device characteristic (e.g., battery voltage) or the result of the nicotine concentration and/or flavorings differing across the liquids used to generate the aerosols. Furthermore, the puffing parameters used by these early pre-clinical studies to generate ECIG aerosols were consistent with that of a tobacco cigarette smoker, but other studies have demonstrated that the puff topography of an experienced ECIG user may differ markedly from that of a tobacco cigarette smoker (Hiler et al, 2017;Spindle et al, 2015). Thus, by not using puffing parameters representative of an experienced ECIG user, the toxicant content of the aerosols generated in these early pre-clinical studies may not be indicative of an ECIG user's actual toxicant exposure.…”
Section: Pre-clinical Analytical Chemistry Examinations Of Ecigssupporting
confidence: 55%
“…The outcomes on craving in this report are supported by recent work with combustible cigarette smokers showing that craving did not change after varying doses of nicotine (similar to those used here) . Notwithstanding, the data in this report do not replicate those reported by Bullen et al and Hiler et al, who showed that e‐cigarettes suppressed nicotine abstinence symptoms in e‐cigarette naïve individuals. Upon completion of this research, another report was published on e‐cigarette naïve individuals showing an asymmetric substitution pattern in which e‐liquid (24 mg/ml) served as a partial substitute for combustible cigarettes but not the reverse.…”
Section: Resultscontrasting
confidence: 49%
“…Following overnight abstinence, there were significant reductions in desire to smoke after an hour of smoking the 16 mg e‐cigarette, however, these reductions were not as great as those seen following the combustible cigarettes. Additionally, a recent study of e‐cigarette naïve users by Hiler et al found that e‐cigarette exposure significantly reduced tobacco craving and withdrawal. Nonetheless, these effects were significantly smaller in magnitude when compared to experienced users.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that use of e-cigarette solutions with nicotine would be associated with subsequent greater frequency of cigarette smoking because nicotine would cause dependence, but differences in cigarettes smoked were small and not statistically significant after adjustment for the type of device used. The level of nicotine in the e-liquid has been shown to impact nicotine delivery, [38][39][40] and previous studies have reported that level of nicotine in e-cigarette e-liquid was associated with frequency of e-cigarette use, cigarette use, and likelihood of cigarette initiation. 17,24 However, no previous studies examining this association have accounted for the type of device used.…”
Section: Discussionmentioning
confidence: 97%